2018
DOI: 10.5530/jyp.2019.11.4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Silver Nanoparticles Addition in Periodontal Dressing For Wound Tissue Healing By 99mTc-ciprofloxacin

Abstract: Objective: Periodontal dressing is a protective material that is used on post-surgical periodontal to protect the surface of the wound and provides a comfort sense to patient. This study was conducted to determine the effect of periodontal dressings containing silver nanoparticles by evaluating inflammatory parameters using 99m Tc-ciprofloxacin; a radiopharmaceutical that can be used for diagnosing infection and inflammation. Methods: This research was carried out using purely experimental 24 male Sprague Dawl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…The mean gingival index showed statistically significant (p<0.05) reduction in Group A from baseline to 3 months. This can be correlated to Prasetyo BC et al [18] who concluded that Coe-Pak dressings with the addition of silver nanoparticles tended to give better results in tissue healing due to anti-inflammatory and antimicrobial properties of silver nanoparticles. Similar, antiinflammatory and antimicrobial effects of silver nanoparticles were demonstrated by Habiboallah G et al [19].…”
Section: Discussionsupporting
confidence: 55%
“…The mean gingival index showed statistically significant (p<0.05) reduction in Group A from baseline to 3 months. This can be correlated to Prasetyo BC et al [18] who concluded that Coe-Pak dressings with the addition of silver nanoparticles tended to give better results in tissue healing due to anti-inflammatory and antimicrobial properties of silver nanoparticles. Similar, antiinflammatory and antimicrobial effects of silver nanoparticles were demonstrated by Habiboallah G et al [19].…”
Section: Discussionsupporting
confidence: 55%
“…There are some side-effects which can consist of adverse tissue reactions and depend on the size and type of the NP Ag [103]. As a side effect, Pokrowiecki noticed a significant decrease in the viability of the cells after exposing human osteoblasts to 0.1 ppm of silver ions by using ToxiLight™ BioAssay Kit after 72 h. The cytotoxic and antibacterial activity can be observed at similar concentration [108].…”
Section: The Antibacterial Activity Of Np Ag-deposited Into Ntt Used mentioning
confidence: 99%
“…There are some side-effects which can consist of adverse tissue reactions and depend on the size and type of the NP Ag [88,103].…”
Section: The Antibacterial Activity Of Np Ag-deposited Into Ntt Used mentioning
confidence: 99%
“…AgNPs were described to contains an antimicrobial influence, by growth factors (Singh et al, 2018). To treat gingival wounds, periodontal treatment coated with AgNPs can be applied (Prasetyo et al, 2019;Yin et al, 2020). AgNPs can be mixed with acrylic resin to stop the development of pathogenic bacterial species like Staphylococcus aureus, E. coli, and Streptococcus mutants (de Castro et al, 2018;Yin et al, 2020).…”
Section: Silver Nanoparticlesmentioning
confidence: 99%